The advantages of e-portfolios in higher education: insights from the students’ feedback - Azmi, Nur Farahiah; Mohamad, Siti Rohana; Jamil, Amira; Abdullah, Tahirah; Hasan, Hazriah (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
The use of an e-portfolio as a tool for learning and assessment has shown a positive effect on the learning process for students. There are many benefits associated with using an e-portfolio for student learning. This research aims to examine the feedback received from students when using an e-portfolio. Data is gathered via e-portfolio assignments via the Google Sites platform, which involved ten e-portfolios written by final year students who enrolled in the Islamic banking and finance course in a higher education institution in East Malaysia. Thematic analysis was employed to evaluate students' feedback on the advantages of using e-portfolios as part of their course assessment. Findings showed that three main themes emerged from the study: better understanding, improved skills and interesting learning. In sum, the utilization of e-portfolio as learning and assessment tools is highly recommended, as e-portfolio improves students’ learning experiences in their studies.